Successful management of acquired pinhole subglottic stenosis by multidisciplinary pediatric airway team - Praveen Khilnani; Chandrashekhar Singha; Ankur Ohri; Rakhee Goyal; Shandip Kumar Sinha; Anup Sabharwal (Wolters Kluwer Medknow Publications, 2021)
The concept of neonatal and pediatric airway team is somewhat new in India. : In Western countries, though this concept has been established recently, it remains only limited to children's hospitals. We report the case of a 15-month-old girl with failure to thrive and critical life-threatening severe subglottic stenosis. She was managed in a comprehensive manner by multidisciplinary pediatric airway team at a tertiary-level children's hospital.